Sublingual Priming with a HIV gp41-Based Subunit Vaccine Elicits Mucosal Antibodies and Persistent B Memory Responses in Non-Human Primates - Bekri, Selma; Bourdely, Pierre; Luci, Carmelo; Dereuddre-Bosquet, Nathalie; Su, Bin; Martinon, Frédéric; Braud, Véronique M.; Luque, Irene; Mateo, Pedro L.; Crespillo, Sara; Conejero-Lara, Francisco; Moog, Christiane; et al. (Frontiers in Immunology, 2017)
Persistent B cell responses in mucosal tissues are crucial to control infection against sexually transmitted pathogens like Human Immunodeficiency Virus 1 (HIV-1). The genital tract is a major site of infection by HIV. Sublingual immunization in mice was previously shown to generate HIV-specific B cell immunity that disseminates to the genital tract. We report here the immunogenicity in female cynomolgus macaques of a sublingual vaccine based on a modified gp41 polypeptide coupled to the cholera toxin B subunit designed to expose hidden epitopes and to improve mucosal retention. Combined sublingual/intramuscular immunization with such muco-adhesive gp41-based vaccine elicited mucosal HIV-specific IgG and IgA antibodies more efficiently than intramuscular immunization alone. This strategy increased the number and duration of gp41-specific IgA secreting cells. Importantly, combined immunization improved the generation of functional antibodies three months after vaccination as detected in HIV-neutralizing assays. Therefore, sublingual immunization represents a promising vaccine strategy to block HIV-1 transmission.